Evaluation of the responsiveness of tulips to mineral fertilizers during early spring forcing in protected ground conditions - I. N. Voronchikhina; O. A. Shchuklina; V. V. Voronchikhin; A. D. Alenicheva; I. N. Klimenkova; N. N. Langaeva; V. E. Kvitko; S. V. Zavgorodny (Овощи России, 2021)
Relevance. When forcing tulips in the early spring period in conditions of protected soil, the effectiveness of fertilizers has not been sufficiently studied. Manufacturers and suppliers of planting material do not give clear recommendations on the timing and doses of the use of mineral fertilizers in the distillation process.Material and methods. The object of study was 6 varieties of tulips of the Dutch selection of the mid-early flowering period. In the experiment, a "9-degree distillation technology"was used. For mineral fertilizing of tulips, a solution of calcium nitrate – Ca(NO3)2 was used in concentrations of 0.1% and 0,2%. The repetition of the experience is fourfold. To assess the effect of fertilizing on the growth and development of tulips, the dynamics of changes in biomorphological indicators was studied: the height of the plants, the diameter of the flower, the mass of cut flowers, as well as the output of commercial products. Results. It was found that the use of calcium nitrate fertilization at a concentration of 0,2% at the early stages of plant development contributes to the formation of a larger cut in the studied varieties, characterized by a high strong stem exceeding the control by 3,83-43,8%, the formation of large peduncles with a diameter of 3,24-5,85 cm and an increase in the yield of marketable products reaching 98%. The profitability of this variant of applying calcium nitrate fertilizing is on average 42% for varieties.Results. It was found that the use of calcium nitrate fertilization at a concentration of 0,2% at the early stages of plant development contributes to the formation of a larger cut in the studied varieties, characterized by a high strong stem exceeding the control by 3,83- 43,8%, the formation of large peduncles with a diameter of 3,24-5,85 cm and an increase in the yield of marketable products reaching 98%. The profitability of this variant of applying calcium nitrate fertilizing is on average 42% for varieties.